Defining contribution of micropore size to hydrogen physisorption behaviors: A new approach based on DFT pore volumes. (March 2019) - Heo, Young-Jung; Yeon, Sun-Hwa; Park, Soo-Jin
Abstract: In recent years, nanoporous materials with high specific surface areas and porosity have been developed to meet the commercial demands of hydrogen storage systems. Subnanometer micropores of less than 1 nm are known for their excellent performances in hydrogen physisorption, but their exact contribution and temperature-dependent adsorption performance are still ambiguous. In this work, we have prepared microporous carbons using Ketjenblack with various micropore size portions via chemical activation. In addition, we propose a new density functional theory (DFT) pore volume-based model to determine the contribution of pore size to gas adsorption. The values of the contribution factor ( k ) derived from the proposed model indicate the effect on the physical adsorption by pore size and are indicated to be inversely proportional to temperature. The proposed model and k values can be used for an important method for ambiguous physical adsorption studies. Graphical abstract: